2019
DOI: 10.1021/acs.energyfuels.9b03746
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methane on Shale: Statistical Physics Model and Site Energy Distribution Studies

Abstract: Adsorption behaviors of methane on four Sichuan Basin shales at different temperatures (318, 338, and 358 K) were experimentally investigated. The adsorption equilibrium data were best fitted by using the modified Hill-monolayer model, in which statistical physics theory was used. Four physicochemical parameters of the number of CH4 molecules per site (n), the density of receptors (N m), total adsorbed quantity (Q a), and energetic parameter (ΔE) were estimated. The thermodynamic potential functions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
(167 reference statements)
0
17
0
Order By: Relevance
“…This number is defined as n (Mobarak et al 2019b;Yazidi et al 2019). The partition function of grand canonical for one adsorption site can be expressed as (Duan et al 2020):…”
Section: Monolayer Model With One Energymentioning
confidence: 99%
See 3 more Smart Citations
“…This number is defined as n (Mobarak et al 2019b;Yazidi et al 2019). The partition function of grand canonical for one adsorption site can be expressed as (Duan et al 2020):…”
Section: Monolayer Model With One Energymentioning
confidence: 99%
“…92 allows these models to be written as a function of ε*. With the differentiating the expression Q e (ε*) with respect to ε*, the approximate SED is obtained (Carter et al 1995;Duan et al 2020;Yan and Niu 2017):…”
Section: Site Energy Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 The main component of shale gas is CH 4 , which is usually stored in underground shale in three different states: free state, adsorbed state, and dissolved state, 4 where the amount of adsorbed gas accounts for up to 85% of the total shale gas reservoir. 5 At a depth of 1500−2500 m underground in Longmaxi Formation shale gas field in China, it was found that the reservoir temperature was approximately 330−360 K, and the gas pressure could well reach 38 MPa. 6 In addition, analysis of the thermodynamic characteristics in the adsorbed phase, based on the results of isothermal adsorption, could improve the understanding of adsorption behavior and enhance the development of shale gas resources.…”
Section: Introductionmentioning
confidence: 99%